UPAYA MENINGKATKAN HASIL BELAJAR IPS MELALUI PENGGUNAAN MEDIA PETA PADA SISWA KELAS V SDN 005 BUKIT TIMAH DUMAI - Masnur Masnur (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
This study aims to describe learning outcomes through the use of map media. This study is a classroom action research, the subject of research is the students of grade V SD 005 Bukit Timah Dumai with the number of 35 students. Based on the results of research stated that student learning outcomes have increased after applied media map on the learning process. This is evidenced by: (a) teacher activity data has increased, in cycle I get score 27 (67,50%) with good category. In cycle II get score 35 (87,50%) with very good category. While the student activity has increased, in cycle I get score 26 (65,00%) with good category. In cycle II obtained a score of 36 (90.00%) with very good category; and (b) the result of IPS study has increased, in the first cycle average student learning outcomes is 70.94 with the number of students who reach KKM amounted to 26 (74.28%) with the category is not complete, in cycle II increased to average student's learning result is 79,08 with number of student reaching KKM amounted to 30 (85,71%) with complete category.